Lip repositioning, a solution for gummy smile - Pardis Haddadi; Hadi Zare; Ali Azadikhah (Tehran University of Medical Sciences, 2021)
For many years oral esthetic problems treated by dentists were limited to those involving the teeth without giving consideration to the gingiva. However, today it is well established that these structures should be in balance to appear esthetically pleasing. More than 3mm gingival show during smiling is considered as 'excessive gingival display' also known as "gummy smile", which is not attractive. The current case series, presents three patients with gummy smile managed by lip repositioning surgery, each with 1 year follow up. Our objective was to introduce lip repositioning as a successful treatment modality to decrease gingival show using a simple and conservative surgical approach.